2012
DOI: 10.1111/j.1469-1795.2012.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape resistance to movement of the poison frog, Oophaga pumilio, in the lowlands of northeastern Costa Rica

Abstract: Conversion of forests to agricultural land or pastures is occurring at a rapid rate in many tropical regions. Amphibians may be particularly susceptible to changes in landscape composition and connectivity because of their physiological characteristics and complex life cycles. We experimentally assessed landscape resistance for the dart‐poison frog Oophaga pumilio associated with two prevalent land‐cover types, secondary forests and pastures, in the northeastern lowlands of Costa Rica. We measured recapture ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 54 publications
4
39
0
Order By: Relevance
“…total basal area, biomass and canopy closure) in forest is not strongly influenced by edge proximity in this system (Nowakowski et al 2013, Schedlbauer et al 2007). To select study trees at each site, we demarcated forest-pasture edges, 100-150 m in length.…”
Section: Sampling Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…total basal area, biomass and canopy closure) in forest is not strongly influenced by edge proximity in this system (Nowakowski et al 2013, Schedlbauer et al 2007). To select study trees at each site, we demarcated forest-pasture edges, 100-150 m in length.…”
Section: Sampling Methodsmentioning
confidence: 84%
“…The study area has a mean annual temperature of 25 ºC and an annual precipitation of ß4 m (Sanford et al 1994). There is still moderate cover of fragmented forest (c. 50% of the landscape), and nearest-neighbour distances between forest patches are typically ࣘ200 m (Nowakowski et al 2013). There is still moderate cover of fragmented forest (c. 50% of the landscape), and nearest-neighbour distances between forest patches are typically ࣘ200 m (Nowakowski et al 2013).…”
Section: Study Area and Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…2(a). This argument is likely to be particularly relevant in the case of Oophaga poison frogs, given the limited dispersal capacity of amphibians (Pyron & Wiens, 2013) and the lower levels of vagility when compared with other taxa (a mark-recapture study in O. pumilio showed that 70% of the recaptured individuals were found < 20 m from the marking site) (Nowakowski et al, 2013). decreased with increasing depth in the species tree, a pattern that is consistent with a predominance of sympatric/parapatric speciation within Central American and South American clades.…”
Section: Geographical Correlates Of Linage Diversification In the Oopmentioning
confidence: 99%
“…Field observations and prior validation of resistance models using an independent abundance data set suggested that cost surfaces derived from species responses to microclimate would be important predictors of landscape genetic structure (Nowakowski et al . , In Press). Fourth, we determined whether the strength of landscape genetic correlations varied across time using land‐cover maps from three different time periods.…”
Section: Introductionmentioning
confidence: 99%